Importance of serum bile acids determination in adolescents with juvenile hyperbilirubinaemia - Kabíček, Pavel (Central European Journal of Public Health, 2004)
The aim of the study was to identify moderate liver impairment in a group of hyperbilirubinaemic adolescents. Using gas chromatography we assessed both total bile acid and primary bile acid levels in 50 adolescents with juvenile hyperbilirubinaemia. At the same time we performed hepatologic examinations and subsequent follow-up assessment of these patients for a period of at least 2 years. As a control group we examined 30 adolescents without any impairment of both the liver and gastrointestinal tract, and 18 patients with low grade (moderately) active chronic hepatitis. In both groups we assessed total and primary bile acids levels as well as conventional liver tests (bilirubin, ALT, AST). On the basis of the clinical course and laboratory findings we divided our patients with juvenile hyperbilirubinaemia into two groups: a group of individuals with Gilbert’s syndrome (30 patients) and a group of individuals with probable moderate liver impairment (20 patients). The latter group consisted of the adolescents who exhibited bilirubinaemia over 90 μmol/l and/or exhibited hepatomegaly or splenomegaly proved by the ultrasound examination and/or exhibited intermittent elevation of the liver aminotransferases serum levels. In the group of individuals with moderate liver impairment serum total bile acid levels were significantly elevated in 26% of patients, and the serum cholic acid level was significantly elevated in 25% of patients. These two parameters mutually correlated at a high level of significance. Juvenile hyperbilirubinaemia is one of the common conditions of adolescent age. Its etiology is diverse; it includes both benign conditions like Gilbert’s syndrome and post-hepatitic and toxic conditions that require a long-term regimen and follow-up examinations. The number of people suffering from juvenile hyperbilirubinaemia has been growing in the population. Currently 4-6% of the adolescent population suffers from this disease. This growing number is probably caused by external factors of our environment (infection, toxic effects). The determination of mild liver disease in hyperbilirubinaemic patients and the provision of an adequate regimen of exercise and adequate nutritional measures is of great importance for the health of the adolescent population.
Keywords: mladiství; Bile Acids and Salts; Hyperbilirubinemia; žlučové kyseliny a soli; hyperbilirubinemie; Gilbertova nemoc; Liver Diseases; poruchy spojené s užíváním psychoaktivních látek; Substance-Related Disorders; nemoci jater; Gilbert Disease; Adolescent